Role of chromatin damage and chromatin trapping of FACT in mediating the anticancer cytotoxicity of DNA-binding small molecule drugs - Nesher, Elimelech (Cancer Res, 2018)
Precisely how DNA-targeting chemotherapeutic drugs trigger cancer cell death remains unclear, as it is difficult to separate direct DNA damage from other effects in cells. Recent work on curaxins, a class of small molecule drugs with broad anticancer activity, show that they interfere with histone-DNA interactions and destabilize nucleosomes without causing detectable DNA damage. Chromatin “damage” caused by curaxins is sensed by the histone chaperone FACT, which binds unfolded nucleosomes becoming trapped in chromatin. In this study, we investigated whether classical DNA-targeting chemotherapeutic drugs also similarly disturbed chromatin to cause chromatin trapping of FACT (c-trapping). Drugs that directly bound DNA induced both chromatin damage and c-trapping. However, chromatin damage occurred irrespective of direct DNA damage and was dependent on how a drug bound DNA, specifically, in the way it bound chromatinized DNA in cells. FACT was sensitive to a plethora of nucleosome perturbations induced by DNA-binding small molecules, including displacement of the linker histone, eviction of core histones, and accumulation of negative supercoiling. Strikingly, we found that the cytotoxicity of DNA-binding small molecules correlated with their ability to cause chromatin damage, not DNA damage. Our results suggest implications for the development of chromatin-damaging agents as selective anticancer drugs.